European constitutional courts and transitions to democracy / Francesco Biagi. - Biagi, Francesco (ASCL studies in comparative law., 2020)
This book brings together research on democratization processes and constitutional justice by examining the role of three generations of European constitutional courts in the transitions to democracy that took place in Europe in the twentieth century. Using a comparative perspective, the author examines how the constitutional courts during that period managed to ensure an initial full implementation of the constitutional provisions, thus contributing - together with other actors and factors - to the positive outcome of the democratization processes. European Constitutional Courts and Transitions to Democracy provides a better understanding of the relationship between transitions to democracy and constitutionalism from the perspective of constitutional courts.